Overcharge and Aging Analytics of Li-Ion Cells. Issue 9 (1st June 2020) - Juarez-Robles, Daniel; Vyas, Anjul Arun; Fear, Conner; Jeevarajan, Judith A.; Mukherjee, Partha P.
Abstract : Overcharge presents a serious safety concern for large scale applications of Li-ion batteries. Despite the availability of several studies of aging-induced and overcharge-induced degradation, there still exists a knowledge gap of what would happen if both degradation mechanisms simultaneously occur. In this work, commercial graphite/LCO pouch cells (5 Ah) are continuously cycled at different upper cutoff voltages, 4.2 through 4.8 V, to elucidate the cumulative effect of the overcharge process on the long-term cycling. As the upper cutoff voltage is extended, the cell gains a higher initial capacity but the cycle life diminishes significantly. Cells overcharged beyond 4.5 V experience significant volume expansion and a high rate of capacity fade, as well as a considerable increase in the temperature and internal resistance. Lithium plating and electrolyte decomposition are observed in cells charged beyond 4.5 V, with SEM-EDS verifying their presence. Electrochemical evidence of both degradation modes appears as a voltage undershoot in the discharge curves. A comparative study of various State of Health (SoH) estimation parameters is presented with the introduction of a new dimensionless SoH indicator, ΦR, based on internal resistance measurement. The proposed degradation number is found to be a good indicator of aggravated degradation in Li-ion cells.